Malaria pigment accelerates MTT – formazan exocytosis in human endothelial cells. Issue 3 (1st October 2018) - D'Alessandro, Sarah; Corbett, Yolanda; Parapini, Silvia; Perego, Federica; Cavicchini, Loredana; Signorini, Lucia; Delbue, Serena; Perego, Carla; Ferrante, Pasquale; Taramelli, Donatella; Basilico, Nicoletta
Abstract: Haemozoin is a by-product of haemoglobin digestion by intraerythrocytic malaria parasites, which induces immunologic responses on different tissues, including endothelial cells. In the present paper, the incubation of human microvascular endothelial cells with haemozoin significantly inhibited MTT reduction, a measure of cytotoxicity, without increasing the release of cytoplasmic lactate dehydrogenase. Moreover, haemozoin did not induce apoptosis or cell cycle arrest nor decreased the number of live cells, suggesting that cells viability itself was not affected and that the inhibition of MTT reduction was only apparent and probably due to accelerated MTT-formazan exocytosis. After 30 min of MTT addition, a significant increase in the % of cells exocytosing MTT formazan crystals was observed in haemozoin-treated cells compared with control cells. Such an effect was partially reversed by the addition of genistein, an inhibitor of MTT-formazan exocytosis. The rapid release of CXCL-8, a preformed chemokine contained in Weibel–Palade bodies, confirmed that haemozoin induces a perturbation of the intracellular endothelial trafficking, including the exocytosis of MTT-formazan containing vesicles. The haem moiety of haemozoin is responsible for the observed effect. Moreover, this work underlines that MTT assay should not be used to measure cytotoxicity induced by haemozoin and other methods should be preferred.